2016
DOI: 10.1111/1365-2478.12366
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of migration‐based location and detection methods for microseismic events

Abstract: Microseismic monitoring in the oil and gas industry commonly uses migration‐based methods to locate very weak microseismic events. The objective of this study is to compare the most popular migration‐based methods on a synthetic dataset that simulates a strike‐slip source mechanism event with a low signal‐to‐noise ratio recorded by surface receivers (vertical components). The results show the significance of accounting for the known source mechanism in the event detection and location procedures. For detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The migration‐based technique, also known as the source‐scanning algorithm (SSA), detects events based on the stacked energy of a characteristic function (e.g., envelope and Short‐time average over long‐time average (STA/LTA) function of continuous waveforms) over gridded potential source locations and origin times (Gharti et al, ; Grigoli et al, , ; Kao & Shan, ; Liao et al, ). It provides robust location estimates of microseismic events even in the presence of strong ambient noise and thereby has been extensively used in surface microseismic monitoring (Drew et al, ; Pesicek et al, ; Trojanowski & Eisner, ). Nevertheless, it is still subject to high false alarm rates, and the location accuracy strongly depends on the local velocity structure.…”
Section: Introductionmentioning
confidence: 99%
“…The migration‐based technique, also known as the source‐scanning algorithm (SSA), detects events based on the stacked energy of a characteristic function (e.g., envelope and Short‐time average over long‐time average (STA/LTA) function of continuous waveforms) over gridded potential source locations and origin times (Gharti et al, ; Grigoli et al, , ; Kao & Shan, ; Liao et al, ). It provides robust location estimates of microseismic events even in the presence of strong ambient noise and thereby has been extensively used in surface microseismic monitoring (Drew et al, ; Pesicek et al, ; Trojanowski & Eisner, ). Nevertheless, it is still subject to high false alarm rates, and the location accuracy strongly depends on the local velocity structure.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic source location is the most crucial step of microseismic processing, and it is needed for subsequent source mechanism inversion and geomechanical analysis. A multitude of studies have been dedicated to the improvement of waveform‐based microseismic location during the past decade (e.g., Anikiev et al, ; Cesca & Grigoli, ; Trojanowski & Eisner, ; L. Li et al, ; Diekmann et al, ; see also Table for a more representative list of references). The main motivation of these studies is to improve locations of the weak microseismic events as the Gutenberg‐Richter (Gutenberg & Richter, ) empirical law implies exponential increase of the number of events if we can locate weaker events.…”
Section: The Rise Of Waveform‐based Location Methodsmentioning
confidence: 99%
“…Cesca and Grigoli () investigated the location performance of different CFs with both synthetic and field mining‐induced seismicity and concluded that kurtosis traces are sensitive with respect to noise, envelope traces produce more stable results but lower imaging resolution, and STA/LTA traces have a better overall performance of location resolution and noise resistance. Trojanowski and Eisner () tested the performance of several CFs with diffraction stacking and cross‐correlation stacking operators, showed the semblance and cross‐correlation stacking have better enhancement of the quality of the stacking profiles, and demonstrated that accounting for the source mechanism by polarization correction improves most efficiently the capability of noise suppression and retrieving weak microseismic events. Beskardes et al () compared the performance of envelope, STA/LTA, and kurtosis with raw waveforms for local earthquakes detection and location.…”
Section: Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations